PENERAPAN SUPERVISI KLINIS KEPALA SEKOLAH UNTUK MENINGKATKAN KEMAMPUAN GURU PADA KEGIATAN BELAJAR MENGAJAR MELALUI MODEL ROLE PLAYING DI SMP - Suntoro Suntoro; Musimin Musimin (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to improve the ability of teachers of SMP Negeri 3 Satu Atap Bangun Purba in applying the role playing model through clinical supervision. This study uses a school action research design with 2 cycles. Each cycle consists of stages of planning, implementation, action, observation and reflection. The subjects of this study were 15 teachers of SMP Negeri 3 Satu Atap Bangun Purba. The research instruments used were clinical supervision instruments, and learning implementation assessment sheets. The results of the study concluded that clinical-based classroom supervision could improve the quality of teacher learning in SMP Negeri 3 Satu Atap Bangun Purba in applying the role playing model through clinical supervision, according to the results of the assessment of the implementation of learning the average was 55.47 in the first cycle and 89.13 in cycle II.